Role of sotalol in rhythm control of atrial fibrillation. Issue 4 (July 2010) - Marinelli, Alessandro; Rosi, Alessandro; Capucci, Alessandro
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in clinical practice and is a major cause of morbidity and mortality. It represents an extremely costly public health problem with a negative impact on the quality of life of patients affected. Despite many drugs that are currently available in preventing recurrences of AF after successful cardioversion to normal sinus rhythm, their efficacy remains unsatisfactory, with a great number of recurrences and several short- and long-term adverse effects. Sotalol is an antiarrhythmic drug with a combination of class II (β-adrenoceptor blocking) and class III (cardiac action potential duration prolongation) properties, making it an attractive option for the treatment and prevention of AF.